Kufal Symbiosis: Collaboration of Artificial Intelligence and Terrorist Organizations - Guna, Wahyu Jati Arya (Security Intelligence Terrorism Journal (SITJ), 2025)
This paper delves into the phenomenon of "kufal symbiosis,” which refers to the collaboration between artificial intelligence (AI) and terrorist organizations. It highlights AI’s potential to enhance the efficiency of terrorist operations. While AI can be used to recruit new members and plan more sophisticated attacks, security agencies face challenges in adapting this technology to counter terrorism effectively. This paper discussed the crucial need to strike a balance between individual privacy and national security, as well as the difficulties of managing large-scale data with limited resources. Additionally, the use of technology such as deepfakes and botnets by terrorist organizations might lead to confusion and intensify the impact of their attacks. The discussion also addresses cyberattacks on smart cities, exposing the vulnerabilities in infrastructure to cyber threats. In conclusion, while AI enhances the efficiency of terrorist operations, it also equips security agencies to prevent such threats despite the ongoing struggle to balance privacy and security.